Non-cardiopulmonary monitoring in thai-ICU (ICU-RESOURCE I study) - Kaweesak Chittawatanarat (2018)
Objective: In addition to cardiopulmonary monitoring, non-cardiopulmonary monitoring (non-CPM) is considered to be an important parameter in intensive care units (ICUs). However, no data on this subject has been reported for Thai ICUs. The objective of the present study is to describe the non-CPM situation in Thai ICUs. Materials and Method: ICU RESOURCE I survey database released during the year 2012 was used for the present study. Non-CPMo refers to neurological monitoring, renal function monitoring, metabolic monitoring, perfusion monitoring and identifying biomarkers. Academic hospital (ACAD), availability grading (AG), numeric frequency grading scale (FGS) and device availability per bed (DPB) were used for categorization of non-CPM collected data. Significant differences between the groups are defined as p<0.05. Results: Advanced monitoring, including; indirect calorimetry, near infrared spectroscopy, peripheral nerve stimulation, gut mucosal tonometry and sublingual side stream dark field imaging are currently unavailable in participating Thai ICUs. All ICUs have devices to measure the levels of capillary glucose, creatinine kinase MB, troponin T and albumin. Bispectral index, ultrasound, continuous renal replacement therapy devices, continuous enteral feeding pumps, intra-abdominal pressure monitoring devices and rectal temperature measuring devices are available in ACAD facilities in greater instances than in other institutions. Similarly; for biomarker and drug level monitoring; procalcitonin, interleukin, brain natriuretic peptide, total creatinine kinase, neutrophilgelatinase-associated lipocalin (NGAL), lactate, central venous oxygen saturation/mixed venous oxygen saturation (ScvO2/SvO2), phenytoin, vancomycin and pre-albumin are used more frequently in ACADs. Gap analysis demonstrating warmer cabins, NGAL, lactate and ScvO2/SvO2show less availability but are frequently used when they have been made available. Intra-abdominal pressure and core temperatures are used less in general ICU practices and are scarcely found. Conclusion: Some of the more advanced non-CPM devices are not found in Thai ICUs. Basic non-CPM devices are available in all ICUs. Some new devices for measurements and for biomarkers are used with greater prevalence in ACAD ICUs. Some measurements including IAP, core temperature, lactate and ScvO2/SvO2) are monitored less frequently in Thai ICUs (Thai Clinical Trial Registry: TCTR-201200005).